Development of graphical user interface for smart irrigation system - Muhammad Arif, Osman (2022)
The agriculture sector must undergo daily monitor that needs to run in precise time to ensure the good quality of the production. Nowadays, climate change had become a serious issue due to the changing led to a big impact on agriculture extension programs to the agriculture sector. Rising temperature and irregular weather patterns impact production and livestock populations. Irrigation imported be closely linked with wateruse efficiency to boost productivity and improve food quality. To develop create a smart irrigation system used Wi-Fi and Radio Frequency to monitor and transmitted information about the system via a graphical user interface. Wi-Fi stands for wireless fidelity, a wireless local area network technology developed for use at home and in small regions. Wi-Fi was referred to as the technology surrounding the radio transmission of internet protocol data from an internet connection to a host computer, and it is the popular moniker for the wireless Ethernet 802.11 b standard for WLANs (Owens & Karygiannis, 2015). Institute of Electrical and Electronics Engineers (IEEE) defined Wi-Fi as a class of certified wireless networking products that adhere to an industry standard known as "802.1 lb"(Al-Alawi & Ismail, 2006). In this system Wi-Fi,HC12(RF) and RTC Module DS3231 is used to control and monitor the irrigation system. This system provide easy to use for tum on and tum off solenoid valve. There are two types of on/off solenoid valve, first is regular tum on and off then it has timer on/off for 5, 7 and 10 minutes. Auto irrigation also have been integrate to the system , system will tum on valve at Sam and 5pm for 10 minutes everyday. There are 4 soil moisture sensor are used in this prototype. All the sensor can be monitor through the IOT Dashboard. The data from the sensor will be send to the microcontroller then the data will be transfer to the IOT Dashboard and SD Card for offline data tracking. The IOT Dashboard can also analyze and view the collected data in the form of graphs, for better understanding. These data can improve the production.